The rejuvenation of the NSP and the rebranding of the SDP: conversations with Singapore`s opposition politicians - James, Kieran; Chia, Roderick; Grant, Bligh; Lee, Dexter (Penerbit UKM, 2011)
Via detailed personal interviews, this paper canvasses the views of leading Singapore oppositional grassroots activists about the state of play in Singapore politics and likely developments over the next ten to fifteen years. We highlight two internet focused activists who have recently switched political parties. Although strong poll performers in 2011, the Workers’ Party of Singapore (WP) has lost three important members from its 2006 campaign – Chia Ti Lik, Goh Meng Seng, and James Gomez. In this paper, Goh and Gomez reflect upon their reasons for leaving WP. Goh points to the lack of emphasis placed by the WP upon internet activism which he views as a strategic error. In one key respect Gomez differs significantly in strategy from Goh. Gomez argues that Goh’s Malay Bureau within the National Solidarity Party (NSP) reflects outdated, old-school politics which can be contrasted sharply with Singapore Democratic Party’s (SDP) post-modern multicultural ethos.